Applicant responses to diversity selection criteria in academic staff position descriptions. Issue 2 (4th March 2019) - Schmaling, Karen B.; Baker, Dana Lee; Blume, Arthur W.; Trevino, Amira Y.
ABSTRACT: Diversifying the academic staff may improve access and participation for underrepresented students; a policy of diversity selection criteria in academic staff position descriptions may advance this goal. This study examined applications to academic staff positions with diversity selection criteria to characterise applicants' responses to such criteria, and the diversity of applicant pools. The 454 applications to 11 research and teaching academic staff positions at a public research university in the United States were coded for references to 9 dimensions of diversity, but nearly 25% of applications contained no such references and were unresponsive to the selection criteria. Ethnicity was mentioned most frequently, followed by references to nonspecific forms of diversity. There were disciplinary differences in references to diversity, and self-disclosures of diversity were rare. These results add to previous work regarding the effectiveness of policies of diversity criteria in academic staff position descriptions and are discussed in terms of suggestions for the search process.